Morbidity Patterns and Health Seeking Behaviour of 50+ Elderly People in the Rural Community at Fateyabad in Chattogram - Farahnaj, Sara; Azim, Mohammed Noorul; Hossain, Mohammed Akram; Mahmud, Sayeed; Datta, Subra Praksh; Mazumder, Pranay Kumar; Ahmed, Mohammad Kawser (IAHS Medical Journal, 2024)
Background: Bangladesh is a nation with 9.3% geriatric population who are above 60 years of age and it is expected to rise to 22% in 2050. Health related problems of the elderly need comprehensive geriatric care. This study aimed to explore the morbidity pattern and its associated factors among the elderly population in a rural area of the Chattogram district of Bangladesh. Materials and methods: A cross-sectional study was conducted at Fateyabad in Hathazari, Chattogram, during the period from April to October 2023 which included 260 respondents aged 50 years and above. Data were collected by face-to-face interview by using a pretested mixed type questionnaire. Data were compiled and analysis were done by using scientific calculator and computer. Results: HTN and Diabetes Mellitus were the most common morbidities among elderly population which was 151 (58%) and 92 (35%) respectively. Female respondents were 143 (55%) and male were 117 (45%). Majority of the elderly population belonged to age group 50-59 which was 160 (61%) years and lion share of the respondents were housewife 134 (51%). The rates of seeking healthcare services was higher among elderly population with primary and secondary education, those living with spouses and children, those residing in extended families with seven or more members and older men and women with diabetes and cardiac diseases. Conclusion: On the basis of the findings, it is suggested that the traditional extended family structure should be sustained, wherein older people are treated with care and respect, thereby promoting health of the aged in rural Bangladesh. Furthermore, family relationships should be strengthened, because older individuals, require emotional and familial support to their end stage of life. IAHS Medical Journal Volume 6(2) December 2023; 64-67